Digitalising the Korean cosmos: representing human–nonhuman continuity and filiality through digital photography in contemporary South Korea. Issue 4 (1st October 2016) - Dugnoille, Julien
Abstract : Since the 1990s, visual anthropology and sociology scholarship has highlighted the radical change that digital technologies have brought to empirical – let alone ethnographic – research in the social sciences. In particular, much attention has been paid to how digital photography, as opposed to analogue photography, has enabled researchers to analyse, transport, store and archive wider visual datasets. However, since the early 1990s when Mitchell famously anticipated the power of digital images as having the potential to produce a new form of visual culture, less has been said on how digital photography has also enabled interlocutors to produce a new visual discourse when they are questioned about their everyday lives by social scientists. In this article, I argue that a focus on the digital photography of human–animal relations in the context of contemporary South Korean society empowers interlocutors with the capability to address and/or express their own views on traditional practices, social change and cultural stereotypes. I will start this article by reproducing my participants' internet aesthetics to show how animal activists use digital technologies (mainly smartphones) to visually frame animal abuse and more-than-human empathy and increase the visibility of violent practices against cats and dogs. I will then show how my interlocutors use digital photography as a way to attest to Korea's social change without having to move away from what they describe as 'traditional Korean values'. Using a Kopytoffian framework, I will then show how participants use photography to 'singularise' the status of livestock animals into that of cosmological responsibility, thereby arguing that digital photography enables my participants to perform and articulate human–animal interactions beyond human terms and human-made categories of life. Finally, I will show how my participants identify identity construction, whether human or nonhuman, as part of a nationalist discourse that draws on cosmologic/geomantic understandings of Korean ethnicity.